2012
DOI: 10.1111/and.12007
|View full text |Cite
|
Sign up to set email alerts
|

Hypo-osmotic test in cat spermatozoa

Abstract: The hypo-osmotic (HOS) test has been used in other species as an indicator of the fertilising capacity of spermatozoa. The aims of this study were to assess the response of domestic cat spermatozoa to the hypo-osmotic test, to determine the type of solution, concentration and time of incubation needed to obtain a maximum percentage of swelling, to correlate the selected combination with the percentages of progressive motility and to evaluate whether dilution of the ejaculate alters the results. Incubation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
0
13
1
2
Order By: Relevance
“…Because these spermatological parameters (motility, HOS test, viability) are dependent on sperm plasma membrane integrity, similar results are expected and their results confirm our results. Although some authors (9,20) found correlation between morphological defect and HOS test, we did not observe any interaction between these parameters. So, these parameters should be evaluated seperately.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Because these spermatological parameters (motility, HOS test, viability) are dependent on sperm plasma membrane integrity, similar results are expected and their results confirm our results. Although some authors (9,20) found correlation between morphological defect and HOS test, we did not observe any interaction between these parameters. So, these parameters should be evaluated seperately.…”
Section: Discussioncontrasting
confidence: 97%
“…Cholesterol is a necessary sterol for cell proliferation and viability. In addition, cholesterol enables cell interactions, affects membrane phase transition, ensures suitable environments for membrane-associated proteins, facilitates morphological membrane characteristics, serves as a membrane antioxidant and decreases membrane permeability by stabilizing the membrane (9).…”
Section: Introductionmentioning
confidence: 99%
“…The hypo‐osmotic (HOS) test used in this study was modified from Comercio et al, (). Briefly, aliquots (5 μl) of each sample (raw ejaculate, simple washed and SLC‐selected) were treated with 50 μl of the hypo‐osmotic (HOS) solution (60 mOsm/kg of fructose solution in sodium citrate) and incubated at 37°C for 45 min.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of these strong correlations between HOST and semen evaluation parameters, HOST was recommended as the semen screening in hospitals for men (Oosterhuis et al ., ) and replacement of routine semen evaluation parameters such as motility, morphology and livability in men (Jayendran et al ., ), boar (Samardžija et al ., ), ram (Bohlooli et al ., ), horse (Neild et al ., ), dog (Rodriguez‐Gil & Rigau, ), goat (Fonseca et al ., ), Spanish free‐range poultry (Santiago‐Moreno et al ., ,b) and cat (Comercio et al ., ). The application of HOST may be an important tool in the routine identification and selection of viable and DNA‐intact individual spermatozoa for ICSI after further research to demonstrate its efficacy and safety (James et al ., ).…”
Section: Significance In Semen Evaluationmentioning
confidence: 97%